2016
DOI: 10.7717/peerj.1685
|View full text |Cite
|
Sign up to set email alerts
|

Flower color preferences of insects and livestock: effects onGentiana luteareproductive success

Abstract: Angiosperms diversification was primarily driven by pollinator agents, but non-pollinator agents also promoted floral evolution. Gentiana lutea shows pollinator driven flower color variation in NW Spain. We test whether insect herbivores and livestock, which frequently feed in G.lutea, play a role in G. lutea flower color variation, by answering the following questions: (i) Do insect herbivores and grazing livestock show flower color preferences when feeding on G. lutea? (ii) Do mutualists (pollinators) and an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The color plays a role as a visual attractant for insects [50]. Krzy żanowski [57] reports that dark green varieties with a high content of chlorophyll a and b and a low level of yellow-orange pigments (flavonols, carotenes, and xanthophylls) are much less accepted by winged forms of grain aphids, and Sobral et al [58] found that herbivorous insects preferred to colonize plants with yellow flowers. In a study by Csanády et al [59], the most preferred colors for hymenopterans were yellow, white, blue, purple, and the least commonly selected color was red; however, these preferences may change depending on the growing season and location.…”
Section: Discussionmentioning
confidence: 99%
“…The color plays a role as a visual attractant for insects [50]. Krzy żanowski [57] reports that dark green varieties with a high content of chlorophyll a and b and a low level of yellow-orange pigments (flavonols, carotenes, and xanthophylls) are much less accepted by winged forms of grain aphids, and Sobral et al [58] found that herbivorous insects preferred to colonize plants with yellow flowers. In a study by Csanády et al [59], the most preferred colors for hymenopterans were yellow, white, blue, purple, and the least commonly selected color was red; however, these preferences may change depending on the growing season and location.…”
Section: Discussionmentioning
confidence: 99%